Combination of small size and carboxyl functionalisation causes cytotoxicity of short carbon nanotubes. Issue 7 (November 2012) - Fröhlich, Eleonore; Meindl, Claudia; Höfler, Anita; Leitinger, Gerd; Roblegg, Eva
Abstract The use of carbon nanotubes (CNTs) could improve medical diagnosis and treatment provided they show no adverse effects in the organism. In this study, short CNTs with different diameters with and without carboxyl surface functionalisation were assessed. After physicochemical characterisation, cytotoxicity in phagocytic and non-phagocytic cells was determined. The role of oxidative stress was evaluated according to the intracellular glutathione levels and protection by N-acetyl cysteine (NAC). In addition to this, the mode of cell death was also investigated. CNTs <8 nm acted more cytotoxic than CNTs ≥20 nm and carboxylated CNTs more than pristine CNTs. Protection by NAC was maximal for large diameter pristine CNTs and minimal for small diameter carboxylated CNTs. Thin (<8 nm) CNTs acted mainly by disruption of membrane integrity and CNTs with larger diameter induced mainly apoptotic changes. It is concluded that cytotoxicity of small carboxylated CNTs occurs by necrosis and cannot be prevented by antioxidants.